2012
DOI: 10.1186/1472-6882-12-180
|View full text |Cite
|
Sign up to set email alerts
|

Association of the UCP-1 single nucleotide polymorphism A-3826G with the dampness-phlegm pattern among Korean stroke patients

Abstract: BackgroundPatients with stroke have various syndromes and symptoms. Through pattern identification (PI), traditional Korean medicine (TKM) classifies the several syndromes and symptoms of stroke patients into five categories: Fire-heat (FH), Dampness-phlegm (DP), Yin-deficiency (YD), Qi-deficiency (QD) and Blood-stasis (BS). DP has been associated with obesity and hyperlipidemia. Uncoupling protein-1 (UCP-1), which plays a major role in thermogenesis and energy expenditure can increase the risk of obesity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Similar studies that show the association between genetic polymorphisms and PI were performed in TKM and TCM17242526. Specifically, the polymorphisms in UCP2 and UCP3, which were significantly associated with BMI and serum cholesterol in Korean female subjects, were also associated with DP pattern242728.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Similar studies that show the association between genetic polymorphisms and PI were performed in TKM and TCM17242526. Specifically, the polymorphisms in UCP2 and UCP3, which were significantly associated with BMI and serum cholesterol in Korean female subjects, were also associated with DP pattern242728.…”
Section: Discussionsupporting
confidence: 70%
“…These results are similar to those previously reported by Min et al . 15 , and other studies showed that DP was significantly related to the obese phenotype 16 17 18 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In contrast, the rs2725220 allele G was associated with hyperuricemia in patients with nonPhlegm block [ 92 ]. In a Korean study on the relationship between gene polymorphisms and Phlegm syndrome, A-3826G and A-1766G polymorphisms in the UCP-1 gene known as obesity-related polymorphisms could be used as candidate genetic markers for the Phlegm-Dampness syndrome in stroke patients [ 98 ]. A self-reported Phlegm pattern questionnaire was developed using the Delphi method, reflecting the opinions of clinical experts in the context of TEAM.…”
Section: Diagnosis Of Phlegm Syndromementioning
confidence: 99%
“…Based on the analysis of gene polymorphism of peripheral blood, Lim et al found that A-3826G and A-1766G uncoupling protein-1 polymorphisms, which are related to obesity, might be candidate genetic markers for the dampness-phlegm syndrome in patients with stroke [ 7 ]. Additionally, Ko et al found that neuropeptide Y (NPY) gene polymorphism was associated with dampness-phlegm syndrome in stroke patients.…”
Section: Studies On the Essence Of Phlegm Syndromementioning
confidence: 99%